Analisis Kebijakan Pemerintahan Terbuka dalam Pelayanan Publik di Kota Denpasar - Agustine, Tities Eka; Prawira, Mohammad Yudha (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2017)
The public services reform is still become an agenda of Indonesian Government. All this time, City government of Denpasar is one of the local government known by integrating public service delivery using technology (E-Government). Nevertheless, there is a new concept that has been developed to improve the government services named Open Government. This concept has three principles, they are policy principle, policy catalyst and policy outcome. Accordance with those terms, the objective of this paper is to provide an analysis of open government policies on public service in Denpasar City. This study is using qualitative method with descriptive approach. The result of this research shows that Denpasar has been achieving the principle of Open Government. The government trying to provide transparency, integrity as well as public participation in accessing public services. The government policies are part of Government of Denpasar’s strong commitment to improve their public service delivery. It’s already stipulated through the mayor’s regulation and mayor’s decree. However, there are several challenges that should be noticed by the City Government of Denpasar. For the massive implementation, they need to provide a legal framework of local regulation and a monitoring and evaluation instrument for public services